Performance Evaluation of the Structure of the Klaten DPRD Building When Affected by a 7.0 Magnitude Earthquake - Hasibuan, Samsul A Rahman Sidik; Karisma, Dwifi Aprillia; Zhafira, Talitha (LPPM Universitas Andalas, 2023)
Evaluation of structural performance in Indonesia has been carried out for several high-rise buildings as part of the owner's demands for safety guarantees to determine the level of security that the building has. A simple but accurate nonlinear analysis is needed to determine the structure's performance under earthquake loads. The capacity spectrum method (pushover analysis) documented in ATC 40 is a form of equivalent linearization based on two basic assumptions: secant period and equivalent damping. The performance point estimates where the capacity of the structure can withstand a given (demand) load; In terms of performance, the level of damage to the structure category based on lateral displacement can be seen. It is simulated that an earthquake will shake the Klaten DPRD building with a magnitude of 7.0 and 20 km from the epicenter. The amount of PGA(g) will be calculated based on the equation of Cornell et al. Building structure modeling was carried out with the help of ETABS v9.7.4.